KAJIAN TENTANG PENGADAAN FASILITAS SOSIAL DALAM PROSES PEMBENTUKAN REGULASI TEMPAT PEMAKAMAN DI DESA CISALAK - Hilman Nur; Muhammad Budi Mulyadi; Baharuddin Jusuf Wirahma (Universitas Suryakancana, 2022)
Cisalak Village is a village located in Cibeber District, Cianjur Regency, has a problem, namely the absence of a legal umbrella that regulates social facilities in the eating process. village laws and regulations and the impact of these regulations. The author in conducting this research uses the Sociological Juridical research method in order to facilitate the data and materials obtained in accordance with what is needed from the object of the problem in this study. Sources of data used in the preparation of this research proposal are primary data and secondary data. Primary data data obtained directly from the people of Cisalak Village. The rights owned by the community are regulated in Law Number 6 of 2014 concerning Villages, secondly, the flow of the village legislation program process is in accordance with Law Number 15 of 2019 concerning the hierarchy of laws and regulations and the authors practice it, as for the impact of the existence of The village regulation has a positive impact on the government and residents of Cisalak village.Keywords: Village, Social Facilities, Cemetery, Law.